(3GdGSJceGd dHjGf ePGgH GdbQGA GdSHYIs - (3CHh GdMSf WGgQ Hf YHO GdefYe Hf YHjO Gddg Hf ZdHhf GdebQj,J (B380 (3g` s
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3bGd CHh GdWjH YHO GdefYe Hf YHOj Gddg Hf ZdHhf GdebQF GdMeO ddg GdPi Ndb GdGTjGA cdgG hGdHQjGJ GYde GjgG GdfGXQ ai cJGHi gPG Cfi fXQJ Edi GdWGdHjf GdbQGAGJ s
(3BNQgG (B:s
(3BNQ GdehLhO aUd ai Gdhba hgh eG hba Ydjg GdcSGFi Ydi eG bHd gGA GdJCfjK ai fMh fYeI hQMeI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs